Spatial distribution patterns of fish assemblages relative to macroinvertebrates and environmental conditions in Andean piedmont streams of the Colombian Amazon. Issue 1 (1st January 2016) - Tobes, Ibon; Gaspar, Sergio; Peláez-Rodríguez, Marlon; Miranda, Rafael
Abstract: This work provides insight into an Andean–Amazonian river system by conducting a comprehensive study of the biodiversity and ecological processes in a poorly studied neotropical freshwater ecosystem. Hacha River in western Colombia harbours a rich and largely unknown biodiversity and is experiencing an increase in anthropogenic impacts from the city of Florencia. Changes in natural habitat characteristics and environmental quality were analysed and related to the distribution of fish and macroinvertebrates. Four environmental quality indices were applied, and concentrations of potential water pollutants were measured. All environmental quality indices used were reliable because they produced similar assessments of the ecological integrity of the study sites and were inversely related to the potential water pollutant concentrations. Fish and macroinvertebrate communities notably changed in response to differences in environmental quality, reinforcing the ecological integrity assessments. Nevertheless, natural gradients that influence fish and macroinvertebrate distributions showed an overlap with changes in environmental quality, thereby confounding the ability to discern the influence of natural and anthropogenic-induced alterations and to confirm an initials hift in fish assemblages due to anthropogenic impacts.